2010
DOI: 10.1159/000281880
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Comorbidities in Patients with Chronic Obstructive Pulmonary Disease

Abstract: Background: Chronic obstructive pulmonary disease (COPD) is associated with many comorbidities, but the percentage of COPD patients who develop comorbidities has not been clearly defined. Objectives: We aimed to examine the relationship between COPD and comorbidities using information obtained from the Health Search Database (HSD) owned by the Italian College of General Practitioners (SIMG), which stores information on about 1.5% of the total Italian population served by general practitioners. Methods: We cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
136
3
10

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(172 citation statements)
references
References 89 publications
23
136
3
10
Order By: Relevance
“…We believe that the most important finding of the present study is that asthma is only weakly associated with cardiovascular and hypertensive diseases, contrary to what is observed in patients with COPD [22]. This might question the importance of the systemic inflammation in asthma, as recent studies have suggested a connection between comorbidities and systemic inflammation in COPD [2][3][4].…”
Section: Discussioncontrasting
confidence: 88%
“…We believe that the most important finding of the present study is that asthma is only weakly associated with cardiovascular and hypertensive diseases, contrary to what is observed in patients with COPD [22]. This might question the importance of the systemic inflammation in asthma, as recent studies have suggested a connection between comorbidities and systemic inflammation in COPD [2][3][4].…”
Section: Discussioncontrasting
confidence: 88%
“…The prevalence of diabetes in COPD patients varies between studies: 10.3% in a population of grade 2/3 COPD patients in a rehabilitation centre according to CRISAFULLI et al [4], 12.6-14.5% in an all-stage COPD population according to MANNINO et al [110], 12.2% with an increased risk in active smokers according to FEARY et al [111] and 18.7% according to CAZZOLA et al [112]. The prevalence of metabolic syndrome is 22.5% for all grades according to GHANASSIA et al [113], and 53% for GOLD grade 2 COPD, 37% for GOLD grade 3 COPD and 44% for GOLD grade 4 COPD according to WATZ et al [114].…”
Section: Epidemiologymentioning
confidence: 99%
“…The systemic consequences that may be related to systemic inflammation include: cardiovascular disease, obesity, hypertension, type 2 diabetes, depression, deconditioning, malnutrition, atrophy and dysfunction of skeletal muscles, physical inactivity, osteoporosis, and anaemia and bone marrow dysfunction [8][9][10][11][12][13][14][15][16][17][18][19][20]. In the last decade, the relationship of comorbidities with systemic inflammation in COPD has been extensively investigated.…”
mentioning
confidence: 99%